Private secretary is among closest subjects of Ruler - Majid, Embun (The Star, 2012)
HAVING spend the past two decades with Tuanku Abdul Halim Mu'adzam Shah, Datuk Paduka Syed Unan Mashri Syed Abdullah holds the distinction of being among the closest subjects of the Ruler.